THE EFFECTS OF SOCIAL MEDIA EXPOSURE, HEDONIC SHOPPING MOTIVATION, AND TRUST IN E-COMMERCE PLATFORMS ON GENERATION Z’S ONLINE CONSUMPTIVE BEHAVIOR IN THE CITY OF MEDAN - Hidayat, Ferry; Angvaline, Valencia; Br Simamora, Rusdiana (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
The development of digital technology and the rapid growth of e-commerce have significantly transformed consumer behavior, particularly among Generation Z, who are highly connected to social media. Exposure to promotional content, digital trends, and the convenience of online transaction has the potential to encourage impulsive and hedonic shopping behavior. This study aims to analyze the influence of social media exposure, hedonic shopping motivation, and trust in e-commerce platforms on the online purchasing behavior of Generation Z in Medan City. This study employs a quantitative approach using a survey method. Primary data were collected through the distribution of questionnaires to Generation Z individuals who actively use social media and engage in online shopping. Data analysis was conducted using statistical techniques, including descriptive analysis as well as partial and simultaneous hypothesis testing. The results indicate that social media exposure, hedonic shopping motivation, and trust in e-commerce platforms have a positive and significant effect on the consumptive behavior of Generation Z, both partially and simultaneously. These findings suggest that higher level of social media exposure, hedonic shopping motivation, and trust in e-commerce platforms are associated with a stronger tendency toward online purchasing behavior among Generation Z in Medan City.